Potential for Sustainable Tourism Development on Rancabali Tea Plantations: Analysis of Social, Economic and Environmental Impact - Zalva Givari; RD Rizki Putra Ramadan (An International Journal Tourism and Community Review, 2024)
The potential for sustainable tourism development in Rancabali Tea Plantation is analyzed from the aspects of social, economic, and environmental impacts. The study reveals that the development of sustainable tourism in Rancabali Tea Plantation can have significant positive impacts on the local community, economy, and environment. Socially, it can create new job opportunities, increase local income, and enrich the local culture. Economically, it can increase the local government's revenue through tourism taxes and the sale of local products, and diversify the local economy through investments in tourism infrastructure. Environmentally, it can promote eco-friendly practices, such as the use of renewable energy, efficient waste management, and the conservation of natural resources. The study concludes that the development of sustainable tourism in Rancabali Tea Plantation has the potential to benefit the local community, economy, and environment, and emphasizes the importance of considering all these aspects in the development of tourism to ensure its long-term success.